How we flipped the medical classroom. (3rd April 2015) - Sharma, Neel; Lau, C. S.; Doherty, Iain; Harbutt, Darren
Abstract: Flipping the classroom centres on the delivery of print, audio or video based material prior to a lecture or class session. The class session is then dedicated to more active learning processes with application of knowledge through problem solving or case based scenarios. The rationale behind this approach is that teachers can spend their face-to-face time supporting students in deeper learning processes. In this paper we provide a background literature review on the flipped classroom along with a three step approach to flipping the classroom comprising implementing, enacting and evaluating this form of pedagogy. Our three step approach is based on actual experience of delivering a flipped classroom at the University of Hong Kong. This initiative was evaluated with positive results. We hope our experience will be transferable to other medical institutions.